Overtourism: the Impact of tourism on Madeira’s social and economic environment - Majdak, Piotr (2022)
The main goal of the analyses presented in the article is to identify the phenomena and consequences concomitant with the phenomenon of overtourism in the economic (with particular emphasis on energy) and social dimensions, regarding the Portuguese island of Madeira. The starting point for considerations includes a review of the issues that define the theoretical framework of “excessive tourism”, as well as a discussion of the most important determinants of the socio-economic development of Madeira. Then, the results of own research are presented, including the original analysis of existing data on electricity production, population growth and the number of overnight stays, as well as the results of a survey conducted in April 20211 , among both permanent residents and tourists visiting the island. The obtained results indicate, among others, that for each increase in the number of overnight stays by 1%, the production of electricity increases by 0.597%; and for every 1% increase in the number of inhabitants, there is a 5.617% increase in electricity production. At the same time, the data on the number of inhabitants indicates a population growth rate close to zero, and thus a higher level of consumption will come from the tourist sector. Based on the results of the survey, key problem areas have been identified (including, for example, issues related to the sense of local identity, security or relations between tourists and residents). The volume of tourist traffic has also been assessed, and a number of reflections and recommendations have been formulated to limit the negative effects of “excessive tourism”.